2019
DOI: 10.1002/iub.2015
|View full text |Cite
|
Sign up to set email alerts
|

Serum exosomal microRNA let‐7i‐3p as candidate diagnostic biomarker for Kawasaki disease patients with coronary artery aneurysm

Abstract: Kawasaki disease (KD) is a systemic vasculitis syndrome that leads to coronary artery aneurysm (CAA). While echocardiography is the most important imaging modality for coronary artery assessment, a specific diagnostic biomarker complementary for CAA has not been reported. We aimed to analyze the profiles of exosomal miRNAs extracted from the serum of KD patients and controls to identify candidate biomarkers for CAA. Serum samples from 39 healthy children, 42 CAA patients, 38 coronary artery dilatation (CAD) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Recent studies by our team have shown that reduced platelet‐derived miR‐223 leads to severe coronary pathology, which promotes vascular smooth muscle cell differentiation and reduces the occurrence of KD complicated with CAA 28 and serum exosomal miR‐Let‐7i‐3p as a new potential biomarker for the diagnosis of KD patients with CAA. 29 KD is an acute systemic vasculitis of unknown etiology that usually affects infants and young children aged under 5 years. 3 Children with severe disease will be complicated by CAAs, leading to a series of cardiovascular sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by our team have shown that reduced platelet‐derived miR‐223 leads to severe coronary pathology, which promotes vascular smooth muscle cell differentiation and reduces the occurrence of KD complicated with CAA 28 and serum exosomal miR‐Let‐7i‐3p as a new potential biomarker for the diagnosis of KD patients with CAA. 29 KD is an acute systemic vasculitis of unknown etiology that usually affects infants and young children aged under 5 years. 3 Children with severe disease will be complicated by CAAs, leading to a series of cardiovascular sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated the relevant role of miRNAs (hsa-let-7i-3p and hsa-miR-409-5p) in the prediction of the early development of ASD or ID alone in TSC patients (AUC 0.894 and 0.880, respectively). Several studies have investigated the role of hsa-let-7i-3p in multiple diseases outside the brain [ 65 , 66 , 67 , 68 ]. On the other hand, the association between hsa-miR-409-5p and neuropsychiatric diseases, such as depression, has been reported in multiple research studies in rodents [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the methylation level of the HAMP promoter significantly decreases in KD, and this hypomethylation feature can serve as biomarkers for KD diagnosis [10]. Our previous studies found that serum exosomal microRNAs could serve as candidate biomarkers in KD [11] and identified microRNAs that are closely related to coronary aneurysms in KD patients [12]. Although methylation and miRNA are sufficiently specific as KD-related diagnostic biomarkers, they may have limited power due to the small sample size of these studies.…”
Section: Introductionmentioning
confidence: 91%